(a+b)²+(a-b)² = 2(a²+b²)Рассмотрим левую часть(a+b)²+(a-b)² = a²+2ab+b²+(a²-2ab+b²) = a²+2ab+b²+a²-2ab+b² =2a²+2b² = 2(a²+b²)Доказано
Ответ:
(а+b)²+(a-b)²=2(a²+b²)
a²+2ab+b²+a²-2ab+b²=2(a²+b²)
2a²+2b²=2(a²+b²)
2(a²+b²)=2(a²+b²) - тождество доказано.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
(a+b)²+(a-b)² = 2(a²+b²)
Рассмотрим левую часть
(a+b)²+(a-b)² = a²+2ab+b²+(a²-2ab+b²) = a²+2ab+b²+a²-2ab+b² =2a²+2b² = 2(a²+b²)
Доказано
Verified answer
Ответ:
(а+b)²+(a-b)²=2(a²+b²)
a²+2ab+b²+a²-2ab+b²=2(a²+b²)
2a²+2b²=2(a²+b²)
2(a²+b²)=2(a²+b²) - тождество доказано.